2005
DOI: 10.1093/nar/gki659
|View full text |Cite
|
Sign up to set email alerts
|

Triplex-induced recombination and repair in the pyrimidine motif

Abstract: Triplex-forming oligonucleotides (TFOs) bind DNA in a sequence-specific manner at polypurine/polypyrimidine sites and mediate targeted genome modification. Triplexes are formed by either pyrimidine TFOs, which bind parallel to the purine strand of the duplex (pyrimidine, parallel motif), or purine TFOs, which bind in an anti-parallel orientation (purine, anti-parallel motif). Both purine and pyrimidine TFOs, when linked to psoralen, have been shown to direct psoralen adduct formation in cells, leading to mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…127 TFO-directed mutations were introduced in somatic cells of mice, validating triplex formation in vivo as well as its mutagenic character in several tissues. 128 It appears that the TFO-induced helical alteration of the duplex provokes the mutagenesis 129 and possibly contributes to common chromosomal translocation in cancer (reviewed in ref. 79).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…127 TFO-directed mutations were introduced in somatic cells of mice, validating triplex formation in vivo as well as its mutagenic character in several tissues. 128 It appears that the TFO-induced helical alteration of the duplex provokes the mutagenesis 129 and possibly contributes to common chromosomal translocation in cancer (reviewed in ref. 79).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…It has been demonstrated that, upon formation, these structures can frequently downregulate (Cooney et al, 1988; Birg et al, 1990; Faria et al, 2000;Faria et al, 2001) and sometimes upregulate (reviewed in Faria and Giovannangeli, 2001) gene expression, a fact which demonstrates their potential in gene control and suggests their use in gene therapy (Wang et al, 1995;Vasquez et al, 2000) (for a review, see Rogers et al, 2005). The structures are also able to impair DNA polymerization (Dayn et al, 1992), and can influence DNA recombination and repair (Faruqi et al, 1996;Wang et al, 1996;Faruqi et al, 2000;Vasquez et al, 2002;Kalish et al, 2005;Raghavan et al, 2005) (for reviews, see Seidman and Glazer, 2003; Chin et al, 2007). Triplexes might also have a role in chromatin organization of both interphase nuclei (Agazie et al, 1996;Ohno et al, 2002) and mitotic chromosomes .…”
mentioning
confidence: 99%
“…In those studies, the TFOs were designed to specifically bind as a third strand in the antiparallel orientation to the polypurine/polypyrimidine triplex target site (30 bp region) in the supFG1 reporter gene. Although various chemical modifications to the backbone, sugars or bases have been developed to improve the bioactivity of TFOs, we used chemical modifications representative of oligonucleotide-based therapeutics currently being investigated in the clinic (Kalish et al, 2005).…”
Section: Discussionmentioning
confidence: 99%